2010
DOI: 10.2174/156652410792630607
|View full text |Cite
|
Sign up to set email alerts
|

Medullary Thyroid Cancer: A Promising Model for Targeted Therapy

Abstract: Abstract:In recent years, the clinical validation of molecular targeted therapies inhibiting the action of pathogenic tyrosine kinase (TK) has been one of the most exciting developments in cancer research. In this context, medullary thyroid carcinoma (MTC) represents a promising model. It is well known that in MTC, the RET receptor TK and its signal transduction pathways, lead to subsequent neoplastic transformation. Several strategies aimed at blocking the activation and signaling of RET have been preclinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 133 publications
(189 reference statements)
0
12
0
Order By: Relevance
“…MEN syndrome includes the following three subtypes: MEN2A (association between medullary thyroid carcinoma [MTC], PHEO and primary hyperparathyroidism); familial medullary thyroid cancer and MEN2B. The latter represents a less common but more aggressive form and it is characterized by the association between MTC and PHEO with other particular features such as mucosal neuromas, intestinal ganglioneuromas, and marfanoid habitus with skeletal deformations and joint laxity [3]. …”
Section: Introductionmentioning
confidence: 99%
“…MEN syndrome includes the following three subtypes: MEN2A (association between medullary thyroid carcinoma [MTC], PHEO and primary hyperparathyroidism); familial medullary thyroid cancer and MEN2B. The latter represents a less common but more aggressive form and it is characterized by the association between MTC and PHEO with other particular features such as mucosal neuromas, intestinal ganglioneuromas, and marfanoid habitus with skeletal deformations and joint laxity [3]. …”
Section: Introductionmentioning
confidence: 99%
“…Activation of the Raf1 signaling pathway has been shown to inhibit growth in SCLC, MTC, and carcinoid cells in vitro [6,25,26], and we showed that doxycycline-induced MEK expression also led to inhibition of cell growth in MTC cells. Taken together, these results suggest that components of the MEK signaling pathway tightly regulate the MTC phenotype.…”
Section: Discussionmentioning
confidence: 56%
“…MTC cells produce several hormones and NE markers such as calcitonin, Chromogranin A (CgA) [5], and Achaete Scute Complex-Like 1 (ASCL1), also known as human ASH1 (Achaete Scute Homolog-1) [6,7]. ASCL1 is involved in C-cell expansion and is critical for neuroendocrine cell differentiation and MTC tumor growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These agents target various tyrosine kinases including MET, RET, and VEGFR-2 (190)(191)(192)(193)(194)(195).…”
Section: Prognosis and Risk Stratification Based On Genetic Testingmentioning
confidence: 99%